2020
DOI: 10.1186/s12904-020-00658-2
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental and affective communication with patients with limited health literacy in the palliative phase of cancer or COPD

Abstract: Background Patients have a ‘need to know’ (instrumental need) and a ‘need to feel known’ (affective need). During consultations with patients with limited health literacy (LHL) in the palliative phase of their disease, both the instrumental and the affective communication skills of healthcare providers are important. The study aims to explore instrumental and affective communication between care providers and LHL patients in the palliative phase of COPD or cancer. Methods In 2018, consultations between LHL p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 30 publications
0
14
0
6
Order By: Relevance
“…There is growing evidence that limited health literacy and low socio-economic status negatively affect patients’ active participation in medical decision-making [ 46 , 47 ]. It has also been shown that doctors primarily use instrumental instead of empathic communication with this group of patients [ 48 ]. In our study, we observed the same tendency.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that limited health literacy and low socio-economic status negatively affect patients’ active participation in medical decision-making [ 46 , 47 ]. It has also been shown that doctors primarily use instrumental instead of empathic communication with this group of patients [ 48 ]. In our study, we observed the same tendency.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were approached by the hospital/research team by phone and when interested met by the research team, prior to the consultation when written consent was obtained. 33 …”
Section: Methods and Analysismentioning
confidence: 99%
“…The e-learning was developed by Dialogue Trainer (technique) and Pharos, Dutch Centre of Expertise on Health Disparities (content), in collaboration with and based on the outcomes of video-observations and subsequent (reflected practice) interviews carried out by Nivel [7,14,20]. For example, quotes from the real-life recorded consultations between HCPs and LHL patients in the palliative phase of their disease were used as input for the scenarios of the e-learning [14]. The goal of the e-learning was to help HCPs in hospital-based care to adapt and improve their communication skills with LHL patients in the palliative phase of their disease.…”
Section: The E-learningmentioning
confidence: 99%
“…So far, limited research has been carried out in palliative care focusing on SDM and LHL patients [13]. Recent research from our team indicates that the assessment of LHL patients' understanding of their situation [14] and the implementation of SDM in palliative care, need improvement [15]. To improve communication and decision-making in hospital-based palliative care, we therefore developed and evaluated a blended training programme for healthcare professionals to improve communication with LHL patients.…”
Section: Introductionmentioning
confidence: 99%